Prolonged liver transplantation survival and aging successfully - Francesco Pollicino; Ligia J. Dominguez; Mario Barbagallo (Geriatric Care, 2023)
The traditional definition of successful aging as the absence of disease, disability, and cognitive impairment is not always applicable to patients with long survival despite complex multimorbidity. This case report details the situation of an 87-year-old man, currently partially self-sufficient and partially autonomous, without cognitive impairment, who has been affected with recurrent right knee osteomyelitis since the age of 6. A diagnosis of hepatitis C virus (HCV)-related liver cirrhosis at 41 led to liver transplantation at 56. The immunosuppressive anti-rejection therapy caused a relapse of chronic osteomyelitis and HCV infection, a major cause of graft loss and shortened survival in HCV liver transplant recipients. Other pathologies were also diagnosed during his lifetime. This patient is an example of aging successfully despite complex multimorbidity and disproves the traditional concept of successful aging formerly described in the literature.